2011
DOI: 10.1097/mbc.0b013e328343f8d7
|View full text |Cite
|
Sign up to set email alerts
|

An uncommon cause of postoperative bleeding

Abstract: The postoperative phase can be associated with an increased risk of thrombosis and abnormal bleeding. We report the case of a patient admitted to our intensive care unit for postoperative monitoring who developed two episodes of hemorrhagic shock. A thromboelastogram performed with heparinase I digestion demonstrated the action of endogenous heparin-like substances whose presence was subsequently confirmed at the histological examination of the tumor. Heparinase-modified thromboelastography has proven to be an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…As a point of care assay, TEG can provide measurements of coagulation and fibrinolysis in 30 min. Berlot et al [7]and Zambruni et al [8] both suggested that TEG is the best method to diagnose endogenous heparin-like substances. The difference between CK-TEG R-time and CKH-TEG R-time is associated with heparin effects, although the difference cannot give a quantitative level of heparin.…”
Section: Discussionmentioning
confidence: 99%
“…As a point of care assay, TEG can provide measurements of coagulation and fibrinolysis in 30 min. Berlot et al [7]and Zambruni et al [8] both suggested that TEG is the best method to diagnose endogenous heparin-like substances. The difference between CK-TEG R-time and CKH-TEG R-time is associated with heparin effects, although the difference cannot give a quantitative level of heparin.…”
Section: Discussionmentioning
confidence: 99%